Compression therapy in lymphedema: Between past and recent scientific data. (September 2019) - Mosti, Giovanni; Cavezzi, Attilio
Aim: To extrapolate and discuss the scientific data on compression in lymphedema treatment, so to review old and innovative concepts about pressure, stiffness and other interplaying factors related to its efficacy and comfort. Material and methods: Narrative review based on search in Medline/Google Scholar through key-words related to compression in lymphedema. Results: Currently available literature lacks relevant details about data on protocol, devices, techniques, interface pressure, stiffness, as well as biases are represented by the different descriptions to present the outcomes. More recent evidence from adjustable wrap devices and elastic garments question the need for high pressure (especially for the upper limb) and stiffness in lymphedema treatment. Conclusions: At present time a very strong compression pressure exerted by material with high stiffness seem to be questionable in lymphedema treatment. A low pressure provides the best outcomes in arm lymphedema, while a pressure in the range of 40–60 mm Hg seems to provide higher efficacy in lower limb lymphedema, provided it is maintained overtime. A high stiffness seems to be unnecessary to treat chronic edema. Future clinical trials, including proper description of treatment methodology and adequate investigating instrumental tools, are awaited to possibly corroborate the conclusive outcomes of our review.